Toxocariasis in Animals and The Risks in Human Being - Estuningsih, S Endah (Indonesian Animal Sciences Society, 2005)
Toxocariasis is usually caused by infection of Toxocara cati to cats, T. canis to dogs and T. vitulorum to cattle or buffaloes. The disease is not recognized and often underestimated by the owners or farmers. Toxocara is a pathogenic gastrointestinal worm and the larva could attack internal organs, cause diarrhea and kill the animals if the disease is not seriously handled . Some species of Toxocara is not only danger to the animals but it could also infect the human being . In human infected by with Toxocara, the larval can cause visceral larval migrans and resulting in symptom such as vomiting. Ocular larval migrans can also result from infection, which causes permanent eye damage in human. Prevention of toxocariasis could be done by avoiding contamination of the environment from eggs, coming from infected animals and also by treating with anthelmintic regularly. Key words: Toxocariasis, Toxocara cati. T. canis, T. vitulorum